The Effect of Thymoquinone and Platelet-Rich Plasma on Intra-Abdominal Adhesions - Gökhan Karaca; Hakan Amioğlu; Mevlüt Recep Pekcici; Huri Demirci (Medicina, 2025)
Background and Objectives: At present, intra-abdominal adhesions (IAAs) continue to be an important problem in surgery due to morbidity and mortality risks. Thymoquinone (TQ) and platelet-rich plasma (PRP) are molecules with known anti-inflammatory and antioxidant effects. However, a limited number of studies have investigated their efficacy in IAAs. In this study, we aimed to demonstrate the efficacy of TQ and PRP in reducing the development of IAAs and determine which molecule is more advantageous using an experimental animal model. Materials and Methods: Fifty-five male Wistar albino rats were included in the study. Five rats were used to obtain PRP, while fifty rats were randomly assigned to five groups (n = 10 per group): group I (sham) did not receive any treatment; group II (control) received no treatment after a cecum hemorrhage procedure; group III (saline) received 1 mL of saline treatment around the cecum after hemorrhage; group IV (PRP) received 1 mL of PRP (containing 3 × 106 platelets/mL) around the cecum after hemorrhage; and group V (TQ) received 1 mL of TQ (containing 2 mg/mL TQ) around the cecum after hemorrhage. On the 10th day, IL1-β, TNF-α, E-selectin, and P-selectin levels were measured from the blood serum samples, and the cecum was histopathologically evaluated. Results: The lowest adhesion formation in terms of biochemical parameters was obtained in the TQ group (p < 0.05). Histopathological evaluations showed that saline, PRP, and TQ treatments were all effective, but none was superior. Conclusions: When histopathologically evaluated, saline, TQ, and PRP have similar effects in IAAs. However, when evaluated in terms of biochemical parameters, TQ prevented the formation of intra-abdominal adhesions more effectively than saline or PRP, owing to its strong anti-inflammatory and antioxidant properties.